ANALISIS PERMINTAAN JASA ANGKUTAN PENUMPANG UDARA DI BANDARA SULTAN SYARIF KASIM II PEKANBARU - Triani Rahmadhani; Wahyu Hamidi; Any Widayatsari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research conducted in Sultan SyarifKasim II Airport in Pekanbaru, the capital city of Riau. The purpose of this research was to determine what factors affect the demand for air transport services on domestic flights and international flights. Data analysis method used in this research is multiple linear regression with statistical test. The results of research on domestic flights for sample F show that GDP per capita for ticket prices of the airline Garuda Indonesia and Lion Air was simultaneously affect the demand for air transport services. Based on sample t is concluded that the GDP per capita for ticket prices of the airline Garuda Indonesia is partially affected and the ticket prices of the airline Lion Air does not partially affect the demand for air transport services on domestic flights. The coefficient of multiple determination for Garuda Indonesia is 0.989, and the coefficient of multiple determination for Lion Air is 0,986. The results of research on international flights for sample F show that the exchange rate and prices simultaneously affect the demand for air transport services. Based on sample t is concluded that the exchange rate and prices is partially affected the demand for air transport services on international flights.The coefficient of multiple determination for Express Air is 0,850.Keyword: Demand, Flights, Ticket Prices, GDP per capita and Exchange Rate.